Perception of the risk of sexual abuse in children from Javier Heraud School, El Tambo - Uribe Hinostroza, Marilú (2019)
The research’s purpose was to know what the perception of children from Javier Heraud School, El Tambo, on risks of child sexual abuse is. It was developed a descriptive level research, basic type and non-experimental design; the instrument used was a questionnaire scale for the study of risk of child sexual abuse. The unit of analysis was the students, between boys and girls, from Javier Heraud School; the population was constituted by 120 students from11-13 years of age attending the 3rd, 4th and 5th grades of primary school, and the sample, by 70 of them. The result for the demonstration of the hypotheses shows significant percentages that fluctuate between 90 % and 98 % of boys and girls that present knowledge and attitudes of prevention against events that could represent risk of sexual abuse. It has been concluded that the perception of children regarding the risks of child sexual abuse puts them in a position of prevention, since they manifest knowledge and adequate information on how to act and react to events of danger; the attitudes they indicate emphasize getting away from people and dubious situations, highlighting the need of communicating with their parents or trusted people.   DOI: https://doi.org/10.31876/sl.v3i1.7